Successively cultivated tomato plants originated from seeds and vegetative propagation in hydroponic system - Fernandes, Adriano Alves; Martinez, Herminia Emilia Prieto; Silva, Derly José Henriques da; Barbosa, José Geraldo; Pedrosa, Adriene Woods (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the origin positions of tomato plant cuttings in the main plant, and to quantify the production and quality of fruits of tomato plants vegetatively propagated, in four successive cultivations, the first one originated from seeds, and the three subsequent ones from cuttings. Data evaluated were: production of fruits per plant; fruit weight; number of fruits per plant; soluble solids; citric acid; and leave and fruit macro and micronutrients contents. The experimental design was in randomized blocks, in a factorial scheme 3x2 (three cuttings plants cultivations x 2 cuttings’ origin positions), with splitplot in time, and six replicates. The cultivations were compared based on the confidence interval of the mean for each evaluated characteristic. The vegetative propagation did not reduce productivity and fruit quality, independently of the cuttings’ origin positions used in the three subsequent cultivations. Either for plant production and fruit quality there were no significant differences among cultivations originated from seed or vegetatively propagated.